If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying xy * dx + -1(2x + 4y) * dy = 0 Multiply xy * dx dx2y + -1(2x + 4y) * dy = 0 Reorder the terms for easier multiplication: dx2y + -1dy(2x + 4y) = 0 dx2y + (2x * -1dy + 4y * -1dy) = 0 dx2y + (-2dxy + -4dy2) = 0 Reorder the terms: -2dxy + dx2y + -4dy2 = 0 Solving -2dxy + dx2y + -4dy2 = 0 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'dy'. dy(-2x + x2 + -4y) = 0Subproblem 1
Set the factor 'dy' equal to zero and attempt to solve: Simplifying dy = 0 Solving dy = 0 Move all terms containing d to the left, all other terms to the right. Simplifying dy = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-2x + x2 + -4y)' equal to zero and attempt to solve: Simplifying -2x + x2 + -4y = 0 Solving -2x + x2 + -4y = 0 Move all terms containing d to the left, all other terms to the right. Add '2x' to each side of the equation. -2x + x2 + 2x + -4y = 0 + 2x Reorder the terms: -2x + 2x + x2 + -4y = 0 + 2x Combine like terms: -2x + 2x = 0 0 + x2 + -4y = 0 + 2x x2 + -4y = 0 + 2x Remove the zero: x2 + -4y = 2x Add '-1x2' to each side of the equation. x2 + -1x2 + -4y = 2x + -1x2 Combine like terms: x2 + -1x2 = 0 0 + -4y = 2x + -1x2 -4y = 2x + -1x2 Add '4y' to each side of the equation. -4y + 4y = 2x + -1x2 + 4y Combine like terms: -4y + 4y = 0 0 = 2x + -1x2 + 4y Simplifying 0 = 2x + -1x2 + 4y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 2*2+y=-5 | | 2*1+y=-5 | | -3x=17+3y-z | | 2*0+y=-5 | | (4x-9)(64x^2-9)=0 | | y^2*dy=x(xdy-ydx)e^x/y | | m^3+2m^2-63m=0 | | 2(2x^2+y^2)*dx-xy*dy=0 | | [x^2+7x-71]=27 | | (2y-5)(3y+7)=0 | | 144=x+38 | | 3x-5(x-3)=-7+2x-10 | | 4*2+y=8 | | p-3u=3k | | 4*1+y=8 | | -3k=3u+-p | | 2(b-24)=44-4(b-4) | | x(x-3)(x+8)=0 | | 4*2-y=0 | | 7(w-5)=28 | | 3x-5=3-7 | | 8(x-5)(x+5)=0 | | 4*1-y=0 | | (3a+8b)(-6)= | | 4*0-y=0 | | -4+6=10 | | 5m+3=19 | | 3(3x^2+y^2)*dx-2xy*dy=0 | | 20log(x)=18.85 | | 5x+2x+5x+40=180 | | 2w-8=-22 | | -3/2y=6 |